2023
DOI: 10.1002/cam4.5588
|View full text |Cite
|
Sign up to set email alerts
|

Application of organoid culture from HPV18‐positive small cell carcinoma of the uterine cervix for precision medicine

Abstract: Background Small cell carcinoma of the uterine cervix (SCCC) is a rare and highly malignant human papillomavirus (HPV)‐associated cancer in which human genes related to the integration site can serve as a target for precision medicine. The aim of our study was to establish a workflow for precision medicine of HPV‐associated cancer using patient‐derived organoid. Methods Organoid was established from the biopsy of a patient diagnosed with HPV18‐positive SCCC. Therapeutic targets were identified by whole exome s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…It is likely that specific culture conditions favour specific mutational loads and the importance of culture conditions on chemoresistance and marker gene expression has been pointed out recently [54]. So far, few other groups have described the establishment of cervical cancer organoids [23, 55, 56]. In our study, patient-derived organoids show clear deviations from immortalized cell lines.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…It is likely that specific culture conditions favour specific mutational loads and the importance of culture conditions on chemoresistance and marker gene expression has been pointed out recently [54]. So far, few other groups have described the establishment of cervical cancer organoids [23, 55, 56]. In our study, patient-derived organoids show clear deviations from immortalized cell lines.…”
Section: Discussionsupporting
confidence: 51%
“…Therefore, our individualised organoid systems, complemented with our newly developed automated readout tools to predict treatment responses, would present an important tool to foster personalised therapy in cervical cancer. In hindsight of our study and the results of others [5456], the optimization of cervical cancer organoid establishment pipelines with the aim of personalized medicine and treatment options should focussed, especially if surgery is excluded as therapeutic option. The direct correlation of driver mutations, protein expression and activation to potential therapy options should be emphasized and pave the way to novel target driven therapies.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Kusakabe et al. found that the fusion of HPV18 and chromosome 8q24.21 was capable of enhancing the expression level of the MYC gene ( 66 ), suggesting that it further promoted the development of tumors because of the role of MYC in accelerating tumor progression. But there was no study about its function in BC.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, CNV analysis showed that the amplification of 3q26.32, 5p15.33 and 8q24.21, and the deletion of 5q21.3, 8p23.2 and 9p21.3 were primarily founded in high-risk patients. Kusakabe et al found that the fusion of HPV18 and chromosome 8q24.21 was capable of enhancing the expression level of the MYC gene (66), suggesting that it further promoted the development of tumors because of the role of MYC in accelerating tumor progression. But there was no study about its function in BC.…”
Section: Discussionmentioning
confidence: 99%